ANALISIS KESIAPAN KERJA MAHASISWA AKUNTASI DI ERA 4.0 MELALUI VARIABEL KEAHLIAN AKUNTANSI DAN LITERASI DIGITAL - Masriyanda Masriyanda; Aldi Fathurrahman; Yofnedi Abrar (Jurnal Akuntansi dan Keuangan (JAK), 2024)
This research aims to explore the interplay between digital literacy, accounting skills, and the employability readiness of prospective accountants in the era of Industry 4.0. By delving into the aspects of digital skills and accounting competencies, the study not only contributes to understanding the dynamics of the accounting profession in the face of technological changes but also adds value to the development of relevant education and training strategies. The data collection method employed in this research involves the use of a questionnaire, with 92 respondents as the sample. The analysis tools utilized include Smart PLS 4.0 and MiniTab 19. The research findings indicate that, partially, accounting skills have a positive and significant influence on employability readiness. Similarly, digital literacy has a positive relationship with employability readiness. Simultaneously, accounting skills and digital literacy jointly influence the employability readiness of prospective accountants.